Tissue-Specific Regulation of Genes by Estrogen Receptors - Leitman, Dale C.; Paruthiyil, Sreenivasan; Yuan, Chaoshen; Herber, Candice B.; Olshansky, Moshe; Tagliaferri, Mary; Cohen, Isaac; Speed, Terence P. (Seminars in Reproductive Medicine, 2012)
Estrogens are frequently used in reproductive medicine. The Women’s Health Initiative trial found that the risks of menopausal hormone therapy (MHT) exceed the benefits. The estrogens in MHT, however, were introduced prior to our understanding of the mechanism of action of estrogens. Estrogen signaling is highly complex, involving various DNA regulatory elements to which estrogen receptors bind. Numerous transcription factors and co-regulatory proteins modify chromatin structure to further regulate gene transcription. With a greater understanding of estrogen action, the major problem with the current estrogens in MHT appears to be that they are nonselective. This produces beneficial effects in bone, brain, and adipose tissue but increases the risk of breast and endometrial cancer and thromboembolism. Resurrecting MHT for long-term therapy will require the development of more selective estrogens, such as estrogen receptor (ER)β-selective estrogens and tissue-selective ERα agonists. These compounds will offer the best prospects to expand the indications of MHT and thus prevent the chronic conditions associated with menopause.
Keywords: estrogen; estradiol; estrogen receptor; gene regulation; transcription